Unique innovative ecotechnologies for protecting from corrosion metal-capacitive structures - Savenko, V.I.; Nesterenko, I.S.; Vysotska, L.M.; Polozskyj, Y.L.; Popkov, V.P. (Ways to Improve Construction Efficiency, 2022)
Currently, corrosion losses in industrialized countries reach 3-5% of national income. This is especially true of metallurgical and chemical enterprises, oil and gas pipelines, watercraft and others, where elements and structures operate in highly aggressive environments of 4-5 degrees. The total damage from corrosion is billions of dollars due to emergencies, environmental disasters and so on. According to statistics, the lack of corrosion protection is the cause of almost 25 percent of accidents As a result of corrosion, metals are converted into various compounds – oxides, hydroxides or salts, in the form of which they are in nature. It is difficult to take into account indirect losses from downtime and reduced productivity of equipment that has undergone corrosion, from disruption of the normal course of technological processes, from accidents caused by reduced strength of metal structures. Up to 10 percent of the produced metal is lost due to corrosion. There are also indirect losses that are difficult to predict or predict. These are losses from downtime and reduced productivity of equipment that has undergone corrosion, from the disruption of normal technological processes, from accidents caused by reduced strength of metal structures, environmental pollution, insurance benefits and, most importantly, from fatalities. Corrosion research suggests that corrosion protection is first and foremost the correct surface preparation and then the sealant or paint. As a result of experiments and tests, the substance CONTRRUST was obtained and patented – a universal eco-material based on plants-modifier-converter, which converts rust into helatic metal polymers. The composition, properties and uses of the material, named and patented as CONTRRUST, have been thoroughly researched and implemented.